Eugenol Induces Phenotypic Alterations and Increases the Oxidative Burst in Cryptococcus - Alves, Júnia C. O.; Ferreira, Gabriella F.; Santos, Julliana R.; Silva, Luís C. N.; Rodrigues, João F. S.; Neto, Wallace R. N.; Farah, Emmanueli I.; Santos, Áquila R. C.; Mendes, Brenda S.; Sousa, Lourimar V. N. F.; Monteiro, Andrea S.; dos Santos, Vera L.; et al. (Frontiers in Microbiology, 2017)
Eugenol is a phenolic compound and the main constituent of the essential oil of clove India. Although there are reports of some pharmacological effects of eugenol, this study is the first that proposes to evaluate the antifungal effects of this phenol against both Cryptococcus gattii and Cryptococcus neoformans cells. The effect of eugenol against yeast cells was analyzed for drug susceptibility, alterations in cell diameter, capsule properties, amounts of ergosterol, oxidative burst and thermodynamics date. Data demonstrated that there is no interaction between eugenol and fluconazole and amphotericin B. Eugenol reduced the cell diameter and the capsule size, increased cell surface/volume, changed positively the cell surface charge of cryptococcal cells. We also verified increased levels of reactive oxygen species without activation of antioxidant enzymes, leading to increased lipid peroxidation, mitochondrial membrane depolarization and reduction of lysosomal integrity in cryptococcal cells. Additionally, the results showed that there is no significant molecular interaction between eugenol and C. neoformans. Morphological alterations, changes of cellular superficial charges and oxidative stress play an important role in antifungal activity of eugenol against C. gattii and C. neoformans that could be used as an auxiliary treatment to cutaneous cryptococcosis.